Herd Evolution as a Forensic Tool - Levy Heleno Fassio; Valdecir Vargas Castilho (Brazilian Journal of Forensic Sciences, Medical Law and Bioethics, 2015)
The livestock sector has been identified as vulnerable to money laundering, according to the National Strategy against Corruption and Money Laundering - ENCCLA. Besides its importance for livestock management, the technic of herd evolution, as used in the present study, may be helpful in solving doubts about the compatibility between the growth or decline of a particular herd and the reproduction and movement of their animals. In this work, proceeded to the evolution of a cattle herd investigated through three scenarios for the period 2000 to 2007. Therefore, Animal Transit Guides (GTAs) and Statements of Vaccination against Foot-and-Mouth Disease (FMD) related to property investigated were used. These documents had, respectively, the record of the moved and vaccinated animals by sex and age group during the analyzed period. The results showed the occurrence of fraud in these livestock records. Therefore, the technic of herd evolution constitutes an important forensic tool, very helpful in combating money laundering through cattle ranching.